2013
DOI: 10.1371/journal.pcbi.1002885
|View full text |Cite
|
Sign up to set email alerts
|

The Human Functional Brain Network Demonstrates Structural and Dynamical Resilience to Targeted Attack

Abstract: In recent years, the field of network science has enabled researchers to represent the highly complex interactions in the brain in an approachable yet quantitative manner. One exciting finding since the advent of brain network research was that the brain network can withstand extensive damage, even to highly connected regions. However, these highly connected nodes may not be the most critical regions of the brain network, and it is unclear how the network dynamics are impacted by removal of these key nodes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 41 publications
7
67
0
Order By: Relevance
“…To this end, we conducted a series of virtual lesion tests assessing the changes in global network efficiency when a targeted network attack (Joyce et al, 2013) was performed on each of the five functional systems, respectively. While individualists generally display higher Global Efficiency (t(27) = 2.13; p = .033), the network attack test shows that inflicting a virtual lesion comprising the cinguloopercular network differentially affects Global Efficiency in individualists and prosocials.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we conducted a series of virtual lesion tests assessing the changes in global network efficiency when a targeted network attack (Joyce et al, 2013) was performed on each of the five functional systems, respectively. While individualists generally display higher Global Efficiency (t(27) = 2.13; p = .033), the network attack test shows that inflicting a virtual lesion comprising the cinguloopercular network differentially affects Global Efficiency in individualists and prosocials.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown decreases in global efficiency with brain aging (Sun, et al, 2012; Tijms, et al, 2013; Wu, et al, 2011; Wu, et al, 2013). Global efficiency is one of the most commonly used measures of network response to targeted attack, including studies of normal and pathologic aging (Crossley, et al, 2014; Crucitti, et al, 2003; Joyce, et al, 2013; Rubinov, et al, 2009; Santarnecchi, et al, 2014). Importantly, global efficiency is associated with increased cognitive reserve in healthy adults (Fischer, et al, 2014; Santarnecchi, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also demonstrate reduced local efficiency associated with normal and pathologic aging (Achard and Bullmore, 2007; Gong, et al, 2009; Sun, et al, 2012; Xiang, et al, 2013). Like global efficiency, local efficiency is a common measure of the brain network's response to computational attack (Joyce, et al, 2013; Santarnecchi, et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…One such property is reflected in the brain's hub architecture, where a small number of nodes have a disproportionately high importance (centrality). Compared to random graphs (wherein all nodes have equivalent importance), graphs with this hub structure tend to be more resilient to random attack (i.e., random removal of edges or nodes) but more vulnerable to targeted attack (i.e., targeted removal of hubs) (Achard et al, 2006; Albert et al, 2000; Joyce et al, 2013). …”
Section: Introductionmentioning
confidence: 99%